Penerapan Terapi Hipnosis Lima Jari Dalam Mengatasi Kecemasan Pada Pasien Hipertensi - Suheimi , Kardimatus; Sari, Endah Purwani; Rahmana, Fatmaricha (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2023)
Background: Hypertension is a disorder of the blood vessels which causes the supply of oxygen carried by the blood to be obstructed to the body tissues that need it. This disease has become a problem in both developed and developing countries. A patient with hypertension may become anxious due to hypertension which tends to require relatively lon treatment. One alternative for relaxation in patients with hypertension is five-finger hypnosis also known as self-hypnosis, which aims to self-programming, relieves anxiety by involving the sympathetic nervous system and will reduce the increas in heart work, breathing, and blood pressure. Objective: To describe the application of five finger hypnosis therapy I overcoming anxiety in hypertensive patients in the village of Tratemulyo Weleri Kendal. Methods: The design of this case study is a pre-experimental research design. The instrument in this case study is the pre-posttest observation sheet. This case study uses 4 subjects and presents the data in the form of narratives and tables. Results: The results of the case study showed that after being given nursing actions for 3 consecutive days in the form of five-finger hypnosis techniques in the four participants there was a decrease in anxiety levels. Conclusion: The results of the case study show that nursing actions in the form of five-finger hypnosis can reduce anxiety in patients with hypertension